2019
DOI: 10.1001/jamanetworkopen.2019.17004
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Route of Hysterectomy for Benign Indications Within an Integrated Health Care System

Abstract: This cross-sectional study examines racial disparities in the route of hysterectomy for benign indications within an integrated health care system in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…We also realize that racial bias exists in hysterectomy route in the United States [19][20][21][22] and evidenced based algorithms and guidelines are needed. Within our institution, we have previously demonstrated how quality improvement initiatives to improve training on MIH was associated with reduced racial disparities in route of MIH 17 .Schmitt et al proposed a decisionmaking algorithm to determine appropriate route of hysterectomy with the goal of optimizing healthcare costs. The execution of the algorithm demonstrated no difference in major complications between LH and VH, however, their study population had limited generalizability with mostly smaller uterine weights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also realize that racial bias exists in hysterectomy route in the United States [19][20][21][22] and evidenced based algorithms and guidelines are needed. Within our institution, we have previously demonstrated how quality improvement initiatives to improve training on MIH was associated with reduced racial disparities in route of MIH 17 .Schmitt et al proposed a decisionmaking algorithm to determine appropriate route of hysterectomy with the goal of optimizing healthcare costs. The execution of the algorithm demonstrated no difference in major complications between LH and VH, however, their study population had limited generalizability with mostly smaller uterine weights.…”
Section: Discussionmentioning
confidence: 99%
“…KPNC serves over 40% of the insured population in Northern California and over one million reproductive-aged women annually, a broad sample of the population of insured adults in Northern California and Kaiser Permanente membership is generally representative of the broader community, primarily differing from the general population by having lower percentages of adults at the low and high income extremes. 17 This study was approved by the KPNC Institutional Review Board with waiver of consent.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen studies with multivariable analyses reported on health care disparity risk markers associated with access to MIS hysterectomy from 2008 to 2020. 4,5,[17][18][19][20][21][22][23][24][25][26][27][28][29] Three controlled for uterine weight, 4,24,28 seven controlled for myoma, 5,[17][18][19][20][21]26,29 and one performed a sensitivity analysis including myomas. 23 The Unauthorized reproduction of this article is prohibited.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (20 models) showed consistent, weak or strong, decreased associations between having a Black racial identity (vs having a White racial identity) and the likelihood of having access to MIS hysterectomy. 4,5,[17][18][19][20][21][22][23][24][26][27][28][29] Similarly, seven studies (nine Unauthorized reproduction of this article is prohibited.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to adequate screening in racially, ethnically, and socioeconomically disadvantaged populations are commonly reported, and in those residing in rural environments with difficult access to health care 8 . Given that many of these barriers are overcome by the standardized screening and equal access to care in an MCO, 9,10 disparities by race were not further investigated for this cohort, but it is an area of future interest at a multicenter level, specifically in this age group population.…”
Section: Discussionmentioning
confidence: 99%